1993
DOI: 10.1128/aac.37.5.991
|View full text |Cite
|
Sign up to set email alerts
|

9-Anilinoacridines as potential antileishmanial agents

Abstract: A number of 1'-substituted 9-anilinoacridines were evaluated for their activities against promastigote and amastigote forms of Leishmania major and for their toxicities to human Jurkat leukemia cells. Several compounds possessing l'-NH-alkyl substituents produced more than 80% growth inhibition of macrophageinfected L. major amastigotes at or below a concentration of 1 ,uM. l'-Hexylamino-9-anilinoacridine (compound 14) was the least toxic compound to human Jurkat cells, while it retained strong antileishmanial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
1
36
0
1
Order By: Relevance
“…Among them, acridine and its derivatives containing a 1,4-dihydropyridine moiety are under constant investigation in view of their profound range of biological activities such as antitumor, 2 antibacterial, 3 antimalarial 4 and antinociceptive activities. 5 The 1,4-naphthoquinone structure is common in numerous natural products associated with antifungal, 6 antibacterial 7 and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, acridine and its derivatives containing a 1,4-dihydropyridine moiety are under constant investigation in view of their profound range of biological activities such as antitumor, 2 antibacterial, 3 antimalarial 4 and antinociceptive activities. 5 The 1,4-naphthoquinone structure is common in numerous natural products associated with antifungal, 6 antibacterial 7 and antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that there is urgent need to search new anticancer agents (Da et al, 1994). Acridine derivatives are one of the more studied chemotherapeutic compounds, widely used as antimalarial, antiprotozoal (Gamage et al, 1997), antibacterial (Mauel et al, 1993), and antitumor agents (Sugaya et al, 1994). Many modifications have been made to the acridine skeleton in the search for anticancer compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The NMR spectra (300 MHz for 1 H and 75.4 MHz for 13 C) were determined in CDCl 3 solution (which also provided the lock signal) on a Bruker AM-300 spectrometer. Assignments of 13 C-NMR chemical shifts were made with the aid of distortionless enhancement by polarization transfer (DEPT) using a flip angle of 135°. IR spectra were run on a Perkin-Elmer 983 G spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Some imidazole, oxazole, and thiazole derivatives are effective against leishmaniasis. 10,11 Carbazolylpyrimidine, 12 9-anilinoacridin, 13 acridinobenzimidazole compounds, 14 and a naturally occurring labdane diterpenoid 15 are also promising antileishmanial agents. A series of organometalic complexes of Pt(II), Pt(IV), Rh(I), Rh(III), Rh(IV), and Sb(III) have also shown antileishmanical activity in vitro.…”
mentioning
confidence: 99%